Gas permeability of films based on low-density polyethylene–ethylene-vinyl acetate blends with cellulosic fillers - P. G. Shelenkov; P. V. Pantyukhov; A. A. Olkhov; A. A. Popov (Тонкие химические технологии)
Objectives. The work set out to characterize the gas permeability properties of biocomposite materials based on synthetic polymers and natural fillers.Methods. The studied materials were blends of low-density polyethylene (LDPE) and ethylene–vinyl acetate (EVA) copolymer, with different LDPE/EVA ratios, as well as biocomposites based on these polymers with natural cellulosic fillers (wood flour (WF) and microcrystalline cellulose (MCC)). The coefficients of gas permeability, diffusion, and oxygen solubility were determined in the obtained composites using the manometric method. The dependence of the diffusion properties of LDPE/EVA blends and biocomposites made of LDPE/EVA/natural filler on the EVA content in the composite was considered.Results. We demonstrated that, as the EVA content in the polymer matrix increases, so also do its solubility and coefficients of gas permeability and oxygen diffusion. The variation in the diffusion characteristics of biocomposite materials obtained using solid filler particles that differ significantly in shape is characterized. The presented interpretation of the obtained results explains the decrease in diffusion in terms of increased rigidity of biocomposites.Conclusions. An increase in the EVA content in blends with LDPE leads to a linear increase in the gas permeability for oxygen, as well as enhanced diffusion and solubility of oxygen in the film. Upon adding a cellulosic filler, the gas permeability of the composites drops almost twofold. The decrease in gas permeability is associated with the morphology of the filler particles increasing the path of gas molecules. Oxygen solubility for composites with MCC and WF is not the same due to the shape of the filler particles. Rough and more elongated WF particles form a more rigid, less permeable structure of the biocomposite than smooth spherical MCC particles.